Delayed Airway Obstruction after Internal Jugular Venous Catheterization in a Patient with Anticoagulant Therapy - Pei-Ju Wu; Siu-Wah Chau; I-Cheng Lu; Hung-Te Hsu; Kuang-I Cheng (Case Reports in Anesthesiology)
Delayed onset of neck hematoma following central venous catheterization without arterial puncture is uncommon. Herein, we present a patient who developed a delayed neck hematoma after repeated attempts at right internal jugular venous puncture and subsequent enoxaparin administration. Progressive airway obstruction occurred on the third day after surgery. Ultrasound examination revealed diffuse hematoma of the right neck, and fibreoptic examination of the airway revealed pharyngeal edema. After emergent surgical removal of the hematoma, the patient was extubated uneventfully.